The Maristan stigma scale: a standardized international measure of the stigma of schizophrenia and other psychoses - Almeida, JM Caldas de (2017)
Background: People with schizophrenia face prejudice and discrimination from a number of sources including professionals and families. The degree of stigma perceived and experienced varies across cultures and communities. We aimed to develop a cross-cultural measure of the stigma perceived by people with schizophrenia. Method: Items for the scale were developed from qualitative group interviews with people with schizophrenia in six countries. The scale was then applied in face-to-face interviews with 164 participants, 103 of which were repeated after 30 days. Principal Axis Factoring and Promax rotation evaluated the structure of the scale; Horn's parallel combined with bootstrapping determined the number of factors; and intra-class correlation assessed test-retest reliability. Results: The final scale has 31 items and four factors: informal social networks, socio-institutional, health professionals and self-stigma. Cronbach's alpha was 0.84 for the Factor 1; 0.81 for Factor 2; 0.74 for Factor 3, and 0.75 for Factor 4. Correlation matrix among factors revealed that most were in the moderate range {[}0.31-0.49], with the strongest occurring between perception of stigma in the informal network and self-stigma and there was also a weaker correlation between stigma from health professionals and self-stigma. Test-retest reliability was highest for informal networks {[}ICC 0.76 {[}0.67 -0.83]] and self-stigma {[}ICC 0.74 {[}0.64-0.81]]. There were no significant differences in the scoring due to sex or age. Service users in Argentina had the highest scores in almost all dimensions. Conclusions: The MARISTAN stigma scale is a reliable measure of the stigma of schizophrenia and related psychoses across several cultures. A confirmatory factor analysis is needed to assess the stability of its factor structure.}}}}}